ATTITUDE OF POLICE TOWARDS CHILDREN IN CONFLICT WITH LAW (International Journal of Food and Nutritional Sciences, 2022)
A child is born with purity and innocence. Nurturing a child is crucial for its growth and development as responsible individual. Positive and supportive environment ensures acceptable behaviours from children. Good physical, psychological, social, moral and spiritual environment make the child a competent person. On the other hand, lack of basic needs, poor parenting supervision, poor educational and social environment leads to delinquency i.e. a Child in Conflict with Law (CCL) .In the India, juvenile delinquency is one of social problems affecting not only children with conflict in law but also families, communities, and society.